Fabrication of α-Fe2O3/In2O3 composite hollow microspheres: A novel hybrid photocatalyst for toluene degradation under visible light - Zhang, F.; Li, Xin Yong; Zhao, Q.; Zhang, Q.; Tadé, M.; Liu, Shaomin (Academic Press Inc., 2015)
The α-Fe2O3/In2O3 composite hollow microspheres were first synthesized through a well-designed two-step hydrothermal approach with an aim to promote the photocatalytic activity of the pure In2O3. The morphologies, phase structures, and optical properties of the resultant samples were systematically characterized by field-emission scanning electron microscopy, transmission electron microscopy, X-ray powder diffraction, X-ray photoelectron spectroscopy, UV–vis diffuse-reflectance, and photoluminescence spectroscopy. The α-Fe2O3 nanoparticles acted as visible-light sensitizer, which were well-decorated on the surface of the In2O3 hollow microspheres. Meanwhile, the investigation of photocatalytic performance confirmed that the visible-light induced photocatalytic degradation rate of gaseous toluene was improved after the introduction of α-Fe2O3 component, which was about 1.6 times higher than that of pure In2O3 sample under identical conditions. Furthermore, some intermediates formed during the photocatalytic oxidation process were also identified by in␣situ FTIR spectroscopy. The enhanced photocatalytic performance of the α-Fe2O3/In2O3 composites mainly stemmed from the strong visible-light-harvesting ability and the efficient spatial separation of photo-generated electron–hole pairs.